Inside the transforming urban Asia processes, policies, and public actions - Mahadevia, Darshini (New Delhi Concept Pub. Co., 2008)
Contributed articles; chiefly with reference to India and China.
Keywords: Urban policy -- India; Urban policy -- China; Urbanization -- India; Urbanization -- China; Globalization -- Social aspects -- India; Globalization -- Social aspects -- China